Designing gamified connected tools for bilingual language therapy and education - Donia Stellini; Daniela R. Gatt; Helen Grech; Philip Farrugia; Edward Abela (Frontiers in Education)
This research contributes to the growing field of technology-enhanced learning by demonstrating how gamification and connected technologies can address gaps in bilingual education and language therapy. It investigates the design, development, and evaluation of Olly’s Adventures: The City of Two Languages, a novel, gamified language intervention tool for bilingual Maltese-English-speaking children aged five to eight. The tool merges a physical board game with a companion mobile application, creating an engaging phygital experience that supports language acquisition across clinical, educational, and home settings. Developed by a multidisciplinary team, the tool was iteratively refined through a user-experience-driven process involving speech and language pathologists, caregivers, educators, design engineers, and children. Mixed-methods data were gathered via focus groups, observations, surveys, and a case study. Findings highlight the tool’s potential to foster language development and increase motivation, with users reporting high levels of engagement, satisfaction, and relevance. Despite limitations related to sample size and the need for clinical validation, the study demonstrates the promise of user-centered connected tools in delivering inclusive, motivating, and linguistically responsive interventions.